Laboratory Assessment of Direct Oral Anticoagulants - Douxfils, Jonathan; Gosselin, Robert C. (Seminars in Thrombosis and Hemostasis, 2017)
Oral vitamin K anticoagulation (warfarin, Coumadin, coumarin) has long been used for long-term treatment and prophylaxis in a variety of clinical settings. Given the unpredictable pharmacokinetic and food impact of warfarin, episodic monitoring is required. Since the early 2000s, direct oral anticoagulants (DOACs) entered into clinical trials as a potential alternative strategy to oral vitamin K antagonists for long-term anticoagulation. As these drugs have predictable pharmacokinetics and pharmacodynamics, there was no requirement for episodic or routine monitoring. However, shortly after their introduction into clinical use, it became apparent that certain emergent or acute situations may require some capacity to measure these drugs, especially in a bleeding patient with DOAC exposure. The scramble for literature and data to support or suggest laboratory methods which can rapidly and accurately quantify or estimate DOAC concentration soon began. This review describes the literature to date, and recommendations for laboratories to provide tests that will assure either the presence/absence of DOAC or the capacity to quantify DOAC using rapid methods that could be implemented on most clinical laboratory instruments.
Keywords: apixaban; dabigatran; edoxaban; rivaroxaban; prothrombin time; activated partial thromboplastin time; dilute thrombin time; Ecarin; anti-Xa